Acute and one year outcome of premature ventricular contraction ablation guided by contact force and automated pacemapping software. Issue 3 (14th May 2019) - Capulzini, Lucio; Vergara, Pasquale; Mugnai, Giacomo; Salghetti, Francesca; Abugattas, Juan Pablo; El Bouchaibi, Said; Iacopino, Saverio; Sieira, Juan; Enriquez Coutiño, Hugo; Ströker, Erwin; Brugada, Pedro; Chierchia, Gianbattista; et al.
Abstract: Background: Radiofrequency (RF) ablation is a well‐established approach to treat premature ventricular contractions (PVC) and is associated with good outcomes. Aim: The present study sought to analyze the acute efficacy and 1‐year outcomes of PVC ablation using RF technology with an approach based on automated pace‐mapping and contact force (CF) information. Methods: Sixty‐one consecutive patients (52.4% males, age 45.9 ± 12.5) underwent catheter ablation for symptomatic monomorphic PVC. All procedures were guided by a 3‐dimensional mapping system; site of ablation was selected based on PASO ™ aided pace‐mapping; RF was started on the selected location when stable catheter position with >10 g of CF were obtained. The procedure was defined as acutely effective if the PVC was eliminated and it did not recur during within 30 minutes. Long‐term efficacy was defined as a decrease by more than 95% at 1 year of the initial PVC burden at ECG Holter monitoring. Results: The PVC ablation was performed in the right ventricular outflow tract in 37 patients (60.7%), left ventricle in 15 patients (24.6%), coronary cusps in 6 patients (9.8%), right ventricle in 3 patients (4.9%); PVC ablation was acutely successful in 59 of patients (96.7%). At 1‐year efficacy was obtained in 57 patients (93.4%). No major complications occurred. Mean procedural and fluoroscopy time were 94.5 ± 20.9 and 4.3 ± 2.5 minutes respectively. Conclusion: Premature ventricular contraction RF ablation mainly guided by PASO ™ and CF showed high success rate in both acute and 1‐year follow‐up (96.7% and 93.4% respectively). The best efficacy cut‐off for RF ablation of PVCs has been identified in presence of both PASO ™ ≥95% and CF >10 g.